Optimization and Performance Analysis of Conventional Boost Converter Topology by Varying Inductor Diameter - Ferdyanto, Ferdyanto; Razi, Muhamad Alif; Armansyah, Armansyah; Hardian, Muhammad Paraj Azhar; Nurhidayat, Panji Sidiq; Liemalasintasari, Liemalasintasari (Department of Physics Education, Universitas Mataram, 2025)
Inductors have a significant influence on the volume, weight, cost, and performance efficiency of converters. In boost converters, the size of the inductor greatly affects the overall size of the converter. In recent years, there has been an increasing number of researches focusing on modeling power losses in magnetic elements and on the influence of power losses in these elements on the characteristics of electronic equipment. Boost converters often operate under non-ideal conditions, when the switch is active for a long period of time (Switch ON), conduction losses increase, high current ripple occurs, and the switch operating cycle is extreme. The magnitude of current ripple in a boost converter will greatly affect the amount of power loss generated in the inductor or MOSFET. Given this, it is important to consider the inductor's ability to overcome power losses that will affect the performance of the boost converter. This research analyzes the effect of inductor size, voltage, current, and efficiency related to the duty cycle. The purpose of this research is to find the highest efficiency by varying the diameter of the inductor wire. The diameter of the inductor wire will affect internal resistance and power dissipation, which will have an impact on the performance of the boost converter. Based on the research results obtained, a diameter of 1.5 achieved the most optimal performance with an efficiency of 69.05. Increasing the diameter of the inductor will improve its ability to store current and reduce internal resistance, thereby overcoming the magnitude of current ripple , reducing power losses due to heat, and converting energy efficiently.